PENGARUH MODEL THINK PAIR SHARE TEMA EKOSISTEM SUBTEMA 1 BERBANTU MEDIA POKI TERHADAP HASIL BELAJAR SISWA KELAS V SDN PENGARADAN 02 BREBES - Indah Sulistiyawati; Rustopo Rustopo; Mudzanatun Mudzanatun (Universitas Negeri Medan, 2018)
Abstract: Influence of Learning Snowball Throwing Assisted Media Puppet onStudent Learning Result of Social Science Class IV SDN 01 Sidomulyo Kendal.The purpose of this study was to determine the effect of the Think Pair Share modelon the theme of Subtitles 1 with the help of Poki media on the learning outcomes ofthe fifth grade students of SDN Pengaradan 02 Brebes. This type of research isquantitative with the experimental method and Pre-Experimental Design. Thesamples taken were all fifth grade students totaling 30 students using theNonprobability Sampling technique in the form of saturated sampling. The results ofthe study showed that there were differences in learning outcomes between studentswho were learning with the Tree Teka-Puzzle (POKI) media-assisted Think PairShare learning model with students learning with conventional learning models.Keywords: Think Pair Share Model, Media Tree Puzzle (POKI), LearningOutcomesAbstrak: Pengaruh Model Think Pair Share Tema Ekosistem Subtema 1Berbantu Media Poki Terhadap Hasil Belajar Siswa Kelas V SDN Pengaradan02 Brebes. Tujuan penelitian ini adalah untuk mengetahui pengaruh model ThinkPair Share tema ekosistem subtema 1 berbantu media Poki terhadap hasil belajarsiswa kelas V SDN Pengaradan 02 Brebes. Jenis penelitian ini adalah kuantitatifdengan metode eksperimen dan Pre-Eksperimental Design. Sampel yang diambiladalah seluruh siswa kelas V yang berjumlah 30 siswa dengan menggunakan teknikNonprobability Sampling berbentuk sampling jenuh. Hasil penelitian menunjukkanbahwa terdapat perbedaan hasil belajar anatara siswa yang belajar dengan modelpembelajaran Think Pair Share berbantu media Pohon Teka-teki (POKI) dengansiswa yang belajar dengan model pembelajaran konvensional.Kata Kunci: Model Think Pair Share, Media Pohon Teka-teki (POKI), HasilBelajar